Carbonized Plant Remains from Loma Salvatierra, Department of Beni, Bolivia - Bruno, Maria C. (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
In this article, we present the results of an analysis of carbonized plant remains from the site of Loma Salvatierra, in the Llanos de Moxos region of Bolivia (Department of Beni). This is the first study of macrobotanical remains from an archaeological site in the region and one of only a few such studies in the Amazon Basin. The identifi ed plant remains include wood, fragments of storage tissues, nuts, and fruits, as well as several seed species. The most common crop encountered was maize, but we also tentatively identified chili pepper, sweet potato, jack bean, peanuts, squash, and cotton. The relatively small sample size made it difficult to confi dently identify changes in plant use through time and space. There are some indications that maize may have decreased in importance through time, while cotton increased. There also appears to be differences in the use and disposal of plants species across the site. This study demonstrates that despite the tropical conditions of the Llanos de Moxos macrobotanical remains can preserve and recovery of such remains should be incorporated into research agendas. The article will be available as a PDF in the near future.